Sistem Informasi Tata Kelola Kantor Pertanahan : Penelitian - Arisman Ismail; Agus Purwanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The land office has an important role in managing agrarian data and services in Indonesia. The problem faced at the Pekalongan City Land Office is the difficulty in controlling the borrowing of land books by staff for certain processes that are still carried out manually or in excel, so that when there is a need for the land book, its whereabouts are difficult to track. This study aims to design and create a land office governance information system called "SITALOKA PERTANAHAN", namely: Land Office Governance Information System, in order to improve service efficiency, transparency, and data accuracy. The method used is a literature study and system analysis based on user needs. The results show that a web-based information system and integrated database can accelerate the land administration process and increase public trust in agrarian services.